2022
DOI: 10.1017/qua.2022.8
|View full text |Cite
|
Sign up to set email alerts
|

The Volchia Griva mineral oasis as unique locus for research of the mammoth fauna and the late Pleistocene environment in Northern Eurasia

Abstract: This paper describes the results of research at Volchia Griva, the largest site in Asia containing mammoth fauna in situ. It is situated in the south of the West Siberian Plain in the Baraba forest-steppe zone, and occupies an area of several hectares. Analysis of sediments and taphonomy of the site allows us to suggest that thousands of megafaunal remains were buried here in mud pits and erosional depressions. The favorable geochemical landscape of Volchia Griva attracted animals during periods of mineral sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 72 publications
(133 reference statements)
3
11
0
Order By: Relevance
“…The mammoth femur and the polar fox cranium from the ABA were studied for δ 13 C and δ 15 N stable isotopic composition of bone collagen. The results are almost identical to the data on the mammoth and canine bones from the 2016 excavation pit, which revealed an abnormal biogeochemical composition of the VG mammalian diet (Leshchinskiy and Burkanova, 2022). Thus, the elevated δ 15 N value (12.50‰) for the mammoth femur is close to the range of 12.86-14.67‰ previously determined for mammoths from the VG lower bone-bearing level.…”
Section: Taphonomy and Paleoenvironmental Conditionssupporting
confidence: 85%
See 3 more Smart Citations
“…The mammoth femur and the polar fox cranium from the ABA were studied for δ 13 C and δ 15 N stable isotopic composition of bone collagen. The results are almost identical to the data on the mammoth and canine bones from the 2016 excavation pit, which revealed an abnormal biogeochemical composition of the VG mammalian diet (Leshchinskiy and Burkanova, 2022). Thus, the elevated δ 15 N value (12.50‰) for the mammoth femur is close to the range of 12.86-14.67‰ previously determined for mammoths from the VG lower bone-bearing level.…”
Section: Taphonomy and Paleoenvironmental Conditionssupporting
confidence: 85%
“…The described deposit differs sharply from most of the VG central faunal accumulation, where there is a record high concentration of large-mammal remains, the vast majority of which belongs to woolly mammoth (Leshchinskiy and Burkanova, 2022). Thus, the taphonomic picture of human activity in the area of the Paleolithic site clearly defines its functional significance and fundamental difference from the natural paleontological burial of megafauna, although there are only a few tens of meters between them.…”
Section: Associated Paleontological Materialsmentioning
confidence: 77%
See 2 more Smart Citations
“…Neural arch depressions have been frequently observed in mammoth remains (Maschenko, 2002; Leshchinskiy and Burkanova, 2003; Maschenko et al, 2006; Krzemińska, 2008; Krzemińska et al, 2015; Leshchinskiy, 2015, 2017), and although it has been suggested that these depressions are specific to mammoths (Krzemińska et al, 2015), the descriptions given here, together with evidence presented by other authors (Leshchinskiy, 2017; Labarca and Pacheco, 2019), indicate that these features are common within various lineages of proboscideans. Several hypotheses regarding the aetiology of these depressions have been proposed, including: a genetic trait (Maschenko, 2002; Maschenko et al, 2006), abnormal bone formation (Musil [1983] as cited in Krzemińska et al, 2015, p. 179), Kashin-Beck disease (Leshchinskiy and Burkanova, 2003; Leshchinskiy, 2012, 2015, 2017), or a calcium-phosphate metabolic disorder resulting from elevated rates of calcium and/or phosphate resorption from bone. This last would probably be linked to malnutrition or mineral deficiency, leading to the transfer of calcium or phosphate from the bones into the blood (Krzemińska et al, 2015).…”
Section: Discussionmentioning
confidence: 99%